Effect of Financial Accountability Practices on Financial Sustainability of Micro Finance Institutions in Garissa County, Kenya - Diis, Abdikadir Salah; Odunga, Robert; Ayora, Joel (International Journal of Finance, 2024)
Purpose: This study aimed at establishing the effect of financial accountability practices on financial sustainability of micro finance institutions in Garissa County, Kenya. Specifically, the study aimed at establishing the effects of financial reporting practices, risk assessment practices, financial structure accountability practices and monitoring activities on financial sustainability of micro finance institutions in Garissa County. Methodology: The study was grounded in three key theories: Accounting Theory, Agency Theory, and Stewardship Theory. It adopted a descriptive research methodology and focuses on eight microfinance institutions in Garissa County. The target population includes 210 employees from departments such as Audit, Finance, and Accounting, along with operational staff, middle-level supervisors, and departmental heads. The study uses a census approach to select all 210 respondents. Both descriptive and inferential statistical methods are utilized for analysis. The analysis was conducted using SPSS version 24 and Microsoft Excel to generate both descriptive and inferential statistics. Tables and figures were employed in displaying the results of the study. Findings: The study established that financial accountability practices comprising of financial reporting practices, risk assessment practices, financial structure accountability practices and monitoring activities positively and significantly affects financial sustainability of micro finance institutions in Garissa, Kenya. This is demonstrated by beta values of 0.176, 0.211, 0.436, and 0.306, along with significant values of 0.019, 0.007, 0.000, and 0.001, respectively. The results bears the implications that increasing each of the financial accountability practices with one unit results to increase in financial sustainability with respective beta values. The study concluded that enhancing the financial accountability practices leads to enhanced financial sustainability of micro finance institutions in Garissa County. Unique Contribution to Theory, Practice and Policy: The study provided recommendations to the management of the MFIs to enhance financial accountability practices such as financial reporting practices, risk assessment practices, financial structure accountability practices and monitoring activities.